The role of top-management in raising international financing - A. A. Tarasov (Управление)
The key aspects of raising corporate finance from the international capital markets are considered in the article. There is an emphasis on the role of the company’s top-management in the important stages of the transaction, including preparation, meeting investors, execution and closing. The basic structural elements of financial instruments, including amount, time, investors and governing law are described. There is a comparison of the financial structure of a syndicated loan and a eurobond across the main parameters, including purpose of the funds, documentation and deal timeline. The roles and functions of the participants of the transaction, including the borrower, banks and advisors, are considered. The key steps of the marketing process such as the roadshow, and the major marketing documents are outlined (the investment presentation and the information memorandum). An important aspect of a successful deal is the presentation of quality analytical and financial materials (financial statements, forecast model, operational overview, strategy, reports of independent market consultants). The deal timeline is also considered, including the preparation phase (kick-off meeting, ratings agencies presentations, Due Diligence), execution (syndication and working with investors, drafting of the legal documentation), and closing of the deal.